(untitled) (Universal International Scientific Journal, 2026)
This article highlights the scientific and pedagogical activities, scientific achievements, and public engagement of female scientists working at Bukhara State Technical University. Their research in technical, pedagogical, and socio-humanitarian areas, their role in educating the younger generation, and the importance of women in the development of science are analyzed.